Інституціональне середовище сталого розвитку - Сокіл, Олег Григорійович; Сокол, Олег Григорьевич; Sokil, Оleh (Мелітополь: ТДАТУ, 2016)
UK: У даній статті досліджено історію визначення та становлення категорій «інституціональне середовище», «інституціональна структура», «інституціональні чинники». Визначено основні складові інституціонального середовища та іх вплив на сталий розвиток. За допомогою попередніх теоретичних досліджень та встановлених стверджень категорії сталого розвитку, сформовано уніфіковане визначення інституціонального середовища сталого розвитку. EN: The primary objective of this work is to describe determination of the incorporated category institutional environment of sustainable development and to define her basic constituents. Research results. In history research of economic sciences was carried out many fundamental openings and statements concerning a institutional study of theory and institutional environment. From other side of research of con-stancy occupy in economic literature and supervisions also a ponderable enough value. However, the empiricist data of two researche directions is low studied and described in literature. The study of institutional environment of sustaina-ble development will enable more wider to understand the problem of constancy, find the factors of her influence and find the ways of effective increase.
Іnstitutional environment of sustainable development
Keywords: інституціональне середовище; інституціональна структура; сталий розвиток; інститут; державна політика; економіка; іnstitutional environment; institutional structure; sustainable development; institute; government policy; economy